Virtual follow-up and care for patients with cardiac electronic implantable devices: protocol for a systematic review - Shannon E. Kelly; Tammy J. Clifford; Doug Coyle; Janet Martin; Vivian Welch; Becky Skidmore; David Birnie; Ratika Parkash; Anthony S. L. Tang; George A. Wells (Systematic Reviews, 2020)
Abstract Background Capacity to deliver outpatient care for patients with cardiac implantable electronic devices (CIEDs) may soon be outweighed by need. This systematic review aims to investigate the comparative effectiveness, safety, and cost for virtual or remote clinic interventions for patients with CIEDs and explores how outcomes may be influenced by patient or system factors in-depth. Methods We will perform a systematic literature search in MEDLINE, Embase, PsycINFO, CINAHL, Proquest Dissertations & Theses, other EBM Reviews, and trial registry databases. Two authors will independently screen titles and abstracts for eligibility. We will include randomized and non-randomized controlled trials, quasi-randomized and experimental studies, cohort, and case-control studies. Study populations of interest are individuals with a CIED (pacemaker, ICD, CRT). Eligibility will be restricted to virtual or remote follow-up or care interventions compared to any other approach. The co-primary outcomes of interest are mortality and patient satisfaction. Secondary outcomes include clinical effectiveness (e.g., ICD shock, time-to-detection of medical event, hospitalizations), safety (e.g., serious or device-related adverse events), device efficacy (e.g., transmissions, malfunctions), costs, workflow (e.g., resources, process outcomes, time-saved), and patient reported (e.g., burden, quality of life). Data will be extracted by one author and checked by a second using a standardized template. We will use published frameworks to capture data relevant to intervention effects that may be influenced by intervention definition or complexity, context and setting, or in socially disadvantaged populations. Detailed descriptive results will be presented for all included studies and outcomes, and where feasible, synthesized using meta-analysis. Risk of bias will be assessed by two review authors independently using Cochrane Risk of Bias tools. Certainty of evidence will be assessed using the GRADE approach. Discussion Increases in number of CIEDs implanted, combined with an aging population and finite health resource allocations at the system-level may lead to increased reliance on virtual follow-up or care models in the future. These models must prioritize consistent, equitable, and timely care as a priority. Results from this systematic review will provide important insight into the potential contextual factors which moderate or mediate the effectiveness, safety, and cost of virtual follow-up or care models for patients. Systematic review registration PROSPERO registration number CRD42020145210